The Role of Heart Rate on the Associations Between Body Composition and Heart Rate Variability in Children With Overweight/Obesity: The ActiveBrains Project - Plaza-Florido, Abel; Migueles, Jairo H.; Mora-Gonzalez, Jose; Molina-Garcia, Pablo; Rodriguez-Ayllon, Maria; Cadenas-Sanchez, Cristina; Esteban-Cornejo, Irene; Navarrete, Socorro; Maria Lozano, Rosa; Michels, Nathalie; Sacha, Jerzy; Ortega, Francisco B. (Frontiers in Physiology, 2019)
Background: Heart rate variability (HRV) is negatively associated with weight status and adiposity in several populations. However, less information is available about this association in children with overweight and obesity, especially severe/morbid obesity, taking into consideration the dependence of HRV on Heart rate (HR). Objectives: 1) to examine associations between body composition measures and HRV, 2) to study differences in HRV between children with overweight and severe/morbid obesity; and 3) to test whether relationships and differences tested in objectives 1 and 2 respectively are explained by the dependency of HRV on HR. Methods: A total of 107 children with overweight/obesity (58% boys, 10.03 ± 1.13 years) participated in this study. Body composition measures were evaluated by Dual-energy X-ray absorptiometry (DXA) and a TANITA bioimpedance balance. HRV parameters were measured with Polar RS800CX®. Results: Body composition measures were negatively associated with HRV indicators of parasympathetic activity (β values ranging from -0.207 to -0.307, all p < 0.05). Children with severe/morbid obesity presented lower HRV values with respect to children with overweight/mild obesity in HRV parameters indicators of parasympathetic activity (p = 0.035). All associations disappeared after further adjustment for HR (all p > 0.05). Conclusion: all associations between adiposity/obesity and HRV seem to be explained by HR, suggesting a key confounding role of HR in HRV studies in children with weight disturbances.